The global pandemic has permanently changed the state of practice for pre-DBS neuropsychological evaluations. (May 2021) - York, M.K.; Farace, E.; Pollak, L.; Floden, D.; Lin, G.; Wyman-Chick, K.; Bobholz, J.; Palmese, C.A.; Racine, C.; Tran, B.; Turner, T.H.; Jimenez-Shahed, J.; et al.
Abstract: The evaluation and management of patients with movement disorders has evolved considerably due to the COVID-19 pandemic, including the assessment of candidates for deep brain stimulation (DBS) therapy. Members of the Neuropsychology Focus Group from the Parkinson Study Group Functional Neurosurgical Working Group met virtually to discuss current practices and solutions, build consensus, and to inform the DBS team and community regarding the complexities of performing DBS neuropsychological evaluations during COVID-19. It is our viewpoint that the practice of neuropsychology has adapted successfully to provide tele-neuropsychological pre-DBS evaluations during the global pandemic, thus permanently changing the landscape of neuropsychological services. Highlights: The COVID-19 pandemic has changed the way in which neuropsychologists conduct pre-DBS evaluations. There are several approaches to pre-DBS tele-neuropsychology evaluations. Despite some limitations, these evaluations can provide helpful information for treatment teams.